Impact of Economic Growth, Foreign Direct Investment and Financial Development on Stock Prices in China: Empirical Evidence from Time Series Analysis - Faisal, Faisal; Majid Muhammad, Peshraw; Tursoy, Turgut (International Journal of Economics and Financial Issues, 2017)
The study aims to empirically examine the dynamic relationship between GDP, stock prices, FDI and domestic credit to the private sector for China by using the ARDL approach for the period 1999Q1:2015Q1. The study confirmed the long-run cointegration among the variables. The empirical results revealed that stock prices and the associated regressors are in a long-term equilibrium relationship; stock prices converge to the long-run equilibrium position by 18.6% speed of adjustment via channel of GDP, stock price, FDI, and domestic credit to the private sector. The findings of the study further revealed that FDI has a positive impact on stock prices in the long-run, while financial development has a negative effect. The robustness of the ARDL bounds test of cointegration was examined by using Johansen and Juselius's (1990) maximum likelihood cointegration approach. Finally, the results of Granger causality under the framework of VECM showed a unidirectional short-run Granger causality that runs from stock prices to economic growth and from economic growth to FDI, specifying the absence of the FDI-led growth hypothesis. Likewise, a bi-directional causality has been found between financial development and stock prices. Keywords: Stock price, ARDL, Cointegration, Granger causality. JEL Classifications: C22, G10, B26